Wide Range Voltage Scaling Converter With Extended Duty and Low Voltage Stress for a DC Microgrid Applications - Md Samiullah; Mohammed Al-Hitmi; Ali T. Al Awami; Shirazul Islam; Atif Iqbal (IEEE Open Journal of Industry Applications)
DC–DC converters hold immense importance due to their diverse applications, making it critical to design them in accordance with the demanding operational requirements. Conventional boost converters face significant challenges at high voltage levels, requiring excessively high duty cycles that lead to increased component stress, switching transients and losses, electromagnetic interference (EMI), and diode reverse recovery issues. This article presents the design of a new voltage scaling converter with applications in high-voltage scenarios, such as the integration of solar photovoltaic (PV) systems into a high-voltage dc bus within a microgrid. The proposed converter features an extendable design and flexible control, enabled by the incorporation of dual duty cycles, allowing for a broader range of operational flexibility. The converter simultaneously achieves high voltage gain, reduced component stress, continuous input current, high power density, and a wide range of feasible duty ratios. The utilization of multiple passive elements is analytically verified by studying variations in parameters, such as the presence of inductors with different values. Finally, the converter's performance is validated through experiments conducted on a 600 W prototype operating at a frequency of 50 kHz. In addition, the closed-loop operation of the converter is validated by its ability to maintain a regulated 400 V dc bus voltage, despite variations in the input voltage.